UPAYA MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V-A PADA MATERI SISTEM ORGAN PERNAPASAN MANUSIA MELALUI METODE PROBLEM BASED LEARNIING BERBANTUAN ALAT PERAGA - Lintang Sekar Putri; Harlinda Syofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to improve student learning outcomes in IPAS class V-A SDN Tanjung Duren Utara 02 Pagi on the material of the human respiratory organ system through the Problem Based Learning method assisted by teaching aids. This research uses the Kemmis and McTaggart model of Classroom Action Research (CAR) approach used in two cycles, with planning, action, observation and reflection as its components. This study involved 30 students from class V-A, comprising 30 male and 17 female pupils. The research results showed an increase in student activity and learning outcomes. In cycle I the percentage of student activity increased from 40.79% to 69.73%, while in cycle II it increased from 84.21% to 94.74%. Student learning completion also increased, from 69% in cycle I to 93% in cycle II. The students' post-test average score increased from 79 in cycle I to 92 in cycle II, exceeding the success indicator of 80%. This improvement in learning outcomes is assisted by teaching aids that make it easier for students to understand, PBL methods that actively involve students, and group discussions that increase students' involvement and critical thinking skills. Thus, the use of the PBL method assisted by teaching aids is effective in improving student learning outcomes in science material.